PENGARUH MODEL LATIHAN KOMBINASI “ONE REALITY TRAINING” UNTUK MENINGKATKAN KEBUGARAN JASMANI BAGI KARYAWAN - Harliawan, Muhammad; Ikadarny, Ikadarny (Program Studi Pendidikan Jasmani, Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dharmas Indonesia, 2026)
This research aims to analyze the impact of the combined training model “One Reality Training” on enhancing the fitness of employees In the modern era, the health and physical well-being of employees have become crucial factors in productivity. The “One Reality Training” model is designed as an integrative method that amalgamates resistance and mobility exercises to improve physical fitness, particularly in muscle strength components. The research methodology for assessing the physical fitness of employees utilizes instruments for measuring muscle strength, incorporating pre-tests and post-tests over a training program spanning 14 sessions. The study participants comprised 26 retail employees who engaged in the “One Reality Training” program. The findings from the 14 sessions of training reveal a significant impact on the enhancement of physical fitness in muscle strength components: upper body strength (push-ups) 0.00<0.05, abdominal strength (sit-ups) 0.000<0.05, leg strength (squats) 0.00<0.05, and posterior leg strength (sumo squats) 0.01<0.05. The conclusion drawn from this research indicates that the combined training model “One Reality Training” is effective in improving employees’ physical fitness in muscle components, thereby positively influencing productivity. Recommendations are made to implement similar training programs sustainably within companies to further support the development of physical fitness and enhance the overall quality of life for employees.